Modeling in advertising A survey study of the impact of the personality appearing in advertising on Iraqi youth (Journal of Imam Al-Kadhim College, 2023)
Abstract :              The Person appearing in advertisements is one of the most important elements in with regard to its design, and it is an effective tool in achieving communication goals because it often depends on the process of stimulating the recipient’s motives towards emulating this character. The most important reasons that drive advertisers to resort to famous artists, football players, athletes, or famous cartoon characters, as well as their recruitment of persons with scientific competence to influence and persuade the recipient of the importance of purchasing the advertised productThe personality appearing in the advertisement is the core of the whole advertisement, and the recipient is attracted, affected, and remembers the advertisement based on the personality that presents it, in addition to its simulation of their personal characteristics, clothes, and actions, regardless of their suitability to the habits, customs, and values ​​of the recipient of the advertising message. This Played by the personality appearing in the advertisement considered as a model that seeks to influence the consumer behavior of the public by simulating the behavior of the personality in consuming the advertised product.With that being said, the research aims to identify the role of this personality in conveying the advertising message and in its ability to attract attention, arouse interest, preserve information and influence the audience's preferences, as well as learn the public how to target it and benefit from the advertised products, thus prompting the public to buy the advertised good and service.The most important finding of this study is that the personality shown in the advertisement makes the product more attractive and helps in remembering the advertisement, especially at the time of seeing the advertised product displayed in the markets, and that this personality has an important influence in learning the recipient how to use the product. As for the most prominent thing that attracts the recipient in the features of the characters shown in the advertisement, is the appearance and clothes that this character.
Keywords: modeling in advertising, apparent personality, persuading the audience